Informed choice of modern Contraceptive Methods and determinant factors among reproductive age women in Eastern Africa countries: A multilevel analysis of demographic and health survey - Gebreeyesus Abera Zeleke; Birtukan Atena Negash; Kassaw Belay Shiferaw; Berhan Tekeba; Tadesse Tarik Tamir; Workie Zemene Worku; Alebachew Ferede Zegeye (PLoS ONE, 2025)
Background Unwanted pregnancies arise from the discontinuation of many contraceptive methods or the failure to use current contraceptive services; this has been a public health concern in Sub-Saharan Africa, particularly in the eastern African countries. Informed choice of modern contraceptive method is an important indicator of family planning quality services. Evidence shows that informed choice of contraceptive methods lowers the potential risk of family planning discontinuation rate, misunderstanding of contraceptive method and unintended pregnancies finally lead to induced abortions. Therefore, the aim of this study was to ascertain the magnitude of informed choice of modern contraceptive methods user and its determinant factors among reproductive age women who are currently using modern contraceptive in Easter African countries. Methods Secondary data analysis was conducted using data from the DHS eight Eastern Africa nations between 2012 and 2020. The total weighted sample was 6154 reproductive age women who used were modern contraceptive method. Stata version 14 was used to analysis secondary data. Determinants of informed choice were determined by using multilevel mixed-effects logistic regression model. Significant factors related with informed choice in multilevel mixed effect logistic regression model were decided when the p value of <0.05. The adjusted odds ratio (AOR) and confidence interval (CI) were used to interpret the outcome. Result In East Africa, the magnitude of informed choice found to be 20.70. determinant factors such maternal age (20–35) years (AOR = 2.02 CI: 1.39, 2.93), (36–49) years (AOR = 2.44, 95% CI: 1.66, 3.61), attending secondary & higher education (AOR = 1.37 95% CI 1.02, 1.84), Media exposure (AOR = 1.25 95% CI 1.05, 1.49), visit health facility within 12 months were (AOR = 1.31 95% CI: 1.11, 1.54) were significantly associated with an informed choice among reproductive age women modern contraceptive method user. Conclusions and recommendation This study concluded that only 20.7% reproductive age women using modern contraceptive method were an informed choice in Eastern Africa. The following factors were strongly linked to informed choice: maternal age, attending secondary and higher education, media exposure, and visiting a health facility within a year. Therefore, policies and initiatives targeting informed choice modern contraceptive methods and above critical determinants among reproductive age women in Eastern Africa (ages 15–49) will be designed by the government, ministry of health, and other relevant parties.